Factors Influencing the Study Period of Students of the Mathematics Study Program at Udayana University - Ulfatun Farika Novitasari; Adinda Audy Sita Mayzandy; Miltiades Dewifortuna Pulo; Juliani Tandi Tumbiri; Nurul Ilma; Made Susilawati (International Journal of Applied Mathematics and Computing, 2025)
The student study period is one of the important aspects to measure the quality of a higher education institution. The length of the student study period can be assumed to come from internal factors and external factors, so it is necessary to conduct research that aims to identify and model the factors that affect the student study period. The method used in this research is logistic regression and the data used is primary data obtained from distributing questionnaires. The target of this research is aimed at alumni students from the Mathematics Study Programme of Udayana University from 2011 to 2019. In this study, the best model produced has a classification accuracy of 98.17% and the independent variables that have a significant effect on the study period are gender, tuition fees and interest in majors.